'Sharing for the memories': Contemporary conceptualizations of memories by young women. (December 2022) - Annabell, Taylor
This article examines how young women conceptualize memories within their language use. Through a microanalysis of how the term 'memories' and related expressions are mobilized by participants in interviews and digital traces shared on platforms, the study offers insight into everyday articulations of memory. The term 'memories' not only denotes the selective reconstruction of the past in the present but also signals how certain experiences, moments and feelings are assessed as worth remembering. Talking about 'memories' becomes a way for young women to signify and anticipate the value of experience in the present and future. In making this argument, the article contributes to existing debates on metaphors of memory and the production of memories through mediated objects by demonstrating how mnemonic language is reconfigured within digital culture.